Driving the Business Service-Oriented Architecture Enabled Initiative - Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing; Abdul-Aziz, Azlianor; Wongsim, Manirath (2011)
Service-oriented architecture (SOA) continues to gain interest and deliver its business value as so many organisations are force to integrate increasingly diverse legacy systems and complex application environments. Organisations are moving towards implementing SOA initiative to become business SOA-enabled for reducing complexity and increasing business agility. Driving the initiative of SOA into business requires a set of requirements in order to successfully implement SOA. These requirements are four fundamentals of SOA initiative with associated seven elements of SOA which have been discovered via thoroughly literature analysis. A model therefore is proposed for businesses to understand how to implement and run SOA to actually achieving benefits from their SOA initiative.